Semiotika Perempuan Dalam Kisah Al-Qurâan - Mardan, Mardan (Fakultas Adab dan Humaniora UIN Alauddin, 2013)
This writing discusses about women semiotics in the stories told in al-Qurâan. The signs of women in al-Qurâan is interisting to study, Â using semiotic approach mainly in understanding the real meaning on women empowerment procces and its implementation in gender perspective. In al-Qurâan there are numbers of symbols pointing out the meaning of womens such is zauj, imraah, umm. Within the pramework of women empowerment, it is neccessary to actualize the quranic exegessis through the stories disclosed in al-Quran that women stand equal with man in any ways except in natural aspect. Al-Qurâan has given large space to women to have double function both domestic and formal.